Respuestas

¡La mejor respuesta!
  • Usuario de Brainly
2013-08-23T21:07:32+02:00
1)    -[5+7.(-3)]+21/7-4
       -[5  - 21]+  3 - 4
      
-[ - 16]+  3 - 4
         + 16 + 3 - 4 =  15

2) 18 /(6.2-3)-(-4).2]
   18/ (-36) - ( - 8) =
       - 1/2 + 8 =
  - 1/2 + 16/2 = 15/2

3) -[5/(-5)+2/(-2)]-10/(3.5-5)
  
-[(-1)+ (- 1)]-10/(15-5)
   -[- 2]-10/(10)
       2 - 1 = 1

Resolver sacando factor común:
  a)   5x(-3)+5x(-2)  = 5x ( -3 - 2 ) = 5x ( - 5)

  b) 6x(-5)-(-4)x(-5)
= (-5)x (6 + 4) = (- 5)x(10)

espero que te sirva,salu2!!!!!